The aneurysmal arteriovenous fistula – morphological study and assessment of clinical implications. A pilot study. (October 2015) - Watson, Kenneth R; Gallagher, Maeve; Ross, Rose; Severn, Alison; Nagy, Janos; Cochrane, Lynda; Griffiths, Gareth D
Aneurysmal dilation of arteriovenous fistulae used for haemodialysis is a recognised complication but its clinical significance is a contentious issue. Our aims were to describe aneurysmal fistulae morphologically and clinically. Sixty patients underwent duplex scanning to measure the maximum diameter and skin thickness of their fistula. Haemodialysis function and bleeding risk were assessed clinically. The 75th percentile of maximum diameter was 2.05 cm. In addition to conventional diameter measurement, we describe a novel volume measurement technique which may be of value. No relationship was found between maximum diameter or volume and function, skin thickness or bleeding. Some studies define aneurysm at 2 cm (75th percentile); however, this definition and other arbitrary definitions lack clinical significance. This work suggests that fistula dilation should be considered together with clinical issues when determining the clinical significance of an aneurysm. Our finding that haemodialysis function, skin thickness and bleeding were not associated with diameter needs further study.